Financial Performance Analysis: A Comparative Study of HUL and Dabur India Limited - Huong, Tran Thi Thu (Journal of Global Economy, Business and Finance, 2026)
Finance is the life blood of any organisation This study analysis the financial performance analysis of two selected FMCG i. e HUL and Dabur India Ltd. This study covers a period of March 2019 to March 2023. This study aims to analyze the liquidity profitability and solvency position of the firm i. e HUL and Dabur India Ltd. The reqd. data were collected from the secondary sources. To study the financial performance of business organisations, ratio analysis are most popularly tool of analyze the financial performance. Ratio analysis means expressing one item in relation to another in numerical term The study reveals that the financial position of both the company is better. The company should Focus. on improving the assets turnover ratio.